Understanding mechanistic relationships between IgG titers and Fc effector functions: a computational framework to assess polyfunctionality - Shoffner-Beck, Suzanne K.; Theisen, Robert M.; Wong, Kade E.; Rerks-Ngarm, Supachai; Pitisuttithum, Punnee; Nitayaphan, Sorachai; Kent, Stephen; Chung, Amy W.; Arnold, Kelly B. (Frontiers in Immunology, 2025)
IntroductionRecent vaccine and infectious disease studies have highlighted the importance of antibodies that activate cellular Fc functions, including antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cellular cytotoxicity (ADCC), which are mediated by different Fc gamma Receptors (FcγRs). Activation of these functions requires complex overlapping interactions between IgG antibodies, FcγRs, and antigens that can be challenging to deconvolve experimentally.MethodsHere we created an ordinary differential equation model that simultaneously predicted FcγRIIIa immune complexes upstream of ADCC and FcγRIIa immune complexes upstream of ADCP as a function of antigen, IgG, and FcγR concentration and binding properties. We then used the model to dissect mechanisms driving immune complex formation.ResultsModel results suggested that the maximum formation of immune complexes would not occur at highest total IgG titers. Instead, higher IgG titers have the potential to decrease FcγRIIIa (ADCC) and/or FcγRIIa (ADCP) immune complexes, due to competition between antibody subclasses for antigen and FcγR binding. We used the model to simulate vaccine boosts of IgG1 or IgG3 in 105 participants from an HIV vaccine trial, and found that boosting IgG1 and IgG3 in combination was not predicted to result in significant changes in either FcγRIIIa (ADCC) or FcγRIIa (ADCP) immune complexes. Surprisingly, simulated boosting of IgG3 alone had the potential to significantly decrease ADCP (p<0.00001), though it would increase ADCC responses. We also illustrated how the model could be used to assess how variability in viral load, FcγR expression, FcγR polymorphisms, and IgG titers across different tissue compartments can lead to differences in FcγRIIIa and FcγRIIa complexes.DiscussionAltogether, these results illustrate how a computational framework provides new quantitative insights into activation of Fc effector functions that could be used to guide future rational design of therapeutic and prophylactic interventions.